1997
DOI: 10.1021/bi9628937
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of a General Class of Mechanism-Based Inhibitors of the Serine Proteinases Employing a Novel Amino Acid-Derived Heterocyclic Scaffold

Abstract: We describe in this paper the structure-based design of a general class of heterocyclic mechanism-based inhibitors of the serine proteinases that embody in their structure a novel peptidomimetic scaffold (1,2,5-thiadiazolidin-3-one 1,1-dioxide). Sulfone derivatives of this class (I) were found to be time-dependent, potent, and highly efficient irreversible inhibitors of human leukocyte elastase, cathepsin G, and proteinase 3. The partition ratios for a select number of inhibitors were found to range between 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
64
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 37 publications
0
64
0
Order By: Relevance
“…These include halo enol lactones, 9À11 b-lactams, 12À16 saccharin derivatives, 17,18 benzoxazinones, 19,20 substituted isocoumarins, 21À23 halomethyldihydrocoumarins 24,25 and thiadiazolidinones. 26,27 We previously described the development of coumarinic derivatives 28 characterized by an alkyl, aryl ester (1) or amide (2) function in the position 3 ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…These include halo enol lactones, 9À11 b-lactams, 12À16 saccharin derivatives, 17,18 benzoxazinones, 19,20 substituted isocoumarins, 21À23 halomethyldihydrocoumarins 24,25 and thiadiazolidinones. 26,27 We previously described the development of coumarinic derivatives 28 characterized by an alkyl, aryl ester (1) or amide (2) function in the position 3 ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore turned our attention to the more polar sulphone counterparts. Aryl sulphonylmethyl moieties have been successfully incorporated into the design of mechanism-based HLE inhibitors, examples of which are the 1,2-benzisothiazol-3(2H)-one 1,1-dioxide [16] and 1,2,5-thiadiazolidin-3-one 1,1-dioxide scaffolds [17][18][19][20][21]. For example, Groutas et al suggested that the latter inactivates HLE via a mechanism involving the departure of the corresponding sulphinic acid to form an electrophilic imine, while the less potent sulphide counterpart leads to acylation of the enzyme without loss of the leaving group [18].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described the design, synthesis, and in vitro biochemical evaluation of a new and general class of mechanism-based inhibitors of serine proteases (structure (I), Figure 1) [17,18], and have recently demonstrated that the time-dependent inactivation of these enzymes by (I) proceeds through the initial formation of a Michael acceptor (a sulfonyl imine), ultimately leading to the formation of an inactive enzyme-inhibitor complex (or complexes) [19]. A key step in the multistep synthesis of (I) was the synthesis of a substituted N-chloromethyl sulfohydantoin via a sulfuryl chloride-mediated cleavage of a phenylthiomethyl ether (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%